Analisis Manajemen Strategi dalam Meningkatkan Daya Saing Rumah Sakit⁠ ⁠ - I Gusti Ngurah Gede Swarga Prawira; Andini Shellawaty Nugraha; Purwadhi Purwadhi; Yani Restiani Widjaja (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The increasing complexity of competition in the healthcare industry requires hospitals to adopt adaptive and strategic management practices to enhance organizational competitiveness. This study aims to analyze the role of strategic management in improving hospital competitiveness through a Systematic Literature Review (SLR) approach. A total of 41 national and international scientific articles published between 2014 and 2025 were reviewed, sourced from Scopus, Web of Science, Google Scholar, and Sinta databases, following the PRISMA guidelines for literature selection. The synthesis of findings indicates that strategic management plays a significant role in strengthening hospital competitiveness through clear strategy formulation, consistent implementation, and continuous performance evaluation. Key factors contributing to competitive advantage include strategic leadership, adaptive organizational culture, effective human resource management, utilization of information technology, and integration between strategic planning and operational processes. The results emphasize that hospitals implementing strategic management comprehensively are better equipped to respond to environmental dynamics, improve service quality, and sustain competitive advantage in the long term. This study highlights the importance of strategic management as a foundational element in modern hospital governance and provides a conceptual basis for future empirical research in healthcare management.